Liquorice, Liddle, Bartter or Gitelman—how to differentiate?. Issue 1 (2nd July 2018) - Mumford, Elizabeth; Unwin, Robert J; Walsh, Stephen B
ABSTRACT: Hypokalaemia with alkalosis can suggest excess aldosterone. Aldosterone stimulates the collecting duct mineralocorticoid receptor (MR) to upregulate the epithelial sodium channel (ENaC) and stimulate electrogenic sodium reabsorption, with secretion of potassium and protons. Gitelman, Bartter and Liddle syndrome, and liquorice ingestion all cause hypokalaemic alkalosis. This mini-review outlines the pathophysiology of these conditions as well as how to differentiate them.